A Validity Analysis of the Reading Test of TPELT, a Developed English Proficiency Test for Primary English Teachers - Agus Syahiddin, - (2023)
This research reported on the validity of the Test for Primary English Language Teachers (TPELT), which was recently developed by a research team at Universitas Pendidikan Indonesia. It was developed to fulfill the needs of a proficiency test for primary English teachers. As a new testing instrument, this test was expected to be examined and evaluated. Therefore, this study aimed to figure out how valid the TPELT reading test was by conducting a priori and a posteriori validity analysis to see the evidence. A qualitative analysis of the relevant test framework and the blueprint of TPELT were analyzed to see whether the test possessed theory-based and context evidence or not. Furthermore, a quantitative approach was employed to analyze the scoring validity. Thirty participants were invited to follow some test trials to obtain test-retest and parallel score analysis. The analysis results showed if TPELT was valid and had the potential to become a high-stakes test and meet the qualifications to be used nationally and internationally. The TPELT Reading Test demonstrates strengths in context validity and score stability over time, aligning with its purpose of assessing the English proficiency of primary teachers in Indonesia. The test includes texts on familiar topics with high-frequency vocabulary, relevant to teachers' English teaching field. The multiple-choice response format ensures easy, fast, and objective scoring. However, improvements are needed, as reliability analysis reveals lower reliability in parallel form and internal consistency of test items, indicating inconsistencies and measurement errors.